Predictors of older schoolchildren’s psychological well-being - Šarakauskienė, Ž.; Bagdonas, A. (Psichologija, 2011)
The rising numbers of the adolescents’ psychological disorders, on the background of limited investments and available psychological services, awake interest in schoolchildren’s psychological well-being. The goal of the study was to determine which sociodemographic and personality variables are significant predictors of the older schoolchildren’s different psychological well-being dimensions. The dimensions of Lithuanian older schoolchildren’s (N = 655, from 21 general and professional education schools) psychological well-being (autonomy (Cronbach’s α = 0.72), environmental mastery (α = 0.62), personal growth (α = 0.60), positive relations with others (α = 0.72), purpose in life (α = 0.67), and self-acceptance (α = 0.74)) were measured, and with the help of multiple linear regression, the psychological well-being was found not to depend on an family composition, living place (41.8% were from five biggest cities, 36.8% from region towns, 21.4% from villages), attendance of extracurricular activities. It wasn’t possible to draw an unambiguous conclusion concerning psychological well-being independence on gender (58% were girls), age, and economic resources. Boys had higher scores than girls in environmental mastery, purpose in life, and self-acceptance, 18-year-old schoolchildren had scored higher than younger ones in personal growth and purpose in life dimensions; the amount of money received for minor expenses had no relationship with the latter two dimensions of psychological well-being. The internal locus of control predicted higher psychological well-being. A higher learning success significantly positively predicted autonomy, personal growth, and purpose in life. Personality variables predicted schoolchildren’s psychological well-being stronger than did sociodemographic ones. Extraversion predicted higher psychological well-being in all six dimensions, and the consciousness factor positively impacted the environmental mastery and purpose in life scores. Emotional stability predicted higher environmental mastery, positive relations with others, and self-acceptance. Neuroticism was unrelated to autonomy and purpose in life. attention must be paid to the fact that the significant prognostic sociodemographic and personality variables analysed in the study accounted for only rather small amounts of psychological well-being dimension variance (from 16.5% in autonomy and personal growth to 28.6% in environmental mastery and positive relations with others).